Characteristics, Antioxidant Activity Stability, and Anti-Fatigue Activity of Hydrolysates from Cucumaria frondosa Tentacles - Mingbo Li; Juan Chen; Qiuting Wang; Chuyi Liu; Wenkui Song; Leilei Sun (Molecules, 2025)
This study aimed to assess the impact of alcalase, trypsin, flavourzyme, and neutrase on the characteristics, antioxidant activity stability, and anti-fatigue activity of hydrolysates derived from Cucumaria frondosa tentacles (CFTHs). The results demonstrate that favourzyme hydrolysates exhibited the highest degree of hydrolysis (DH). Zeta potential and particle size measurements indicated that hydrolyzed peptides treated with favourzyme appeared aggregated and exhibited larger particle sizes. The antioxidant properties of CFTHs demonstrated good thermal stability, pH stability, and enhanced simulated gastrointestinal digestive stability. The anti-fatigue activity of CFTHs was examined using an acute exercise fatigue model. The results indicate that CFTHs extended the exhaustive swimming time of mice to 17.81 min. Additionally, CFTHs significantly elevated (p < 0.01) blood glucose (Glu) and liver glycogen (LG) levels, while also decreasing (p < 0.05) the concentrations of metabolites such as lactic acid (LA), urea nitrogen (BUN), creatine kinase (CK), lactate dehydrogenase (LDH), and ammonia (NH3). This reduction contributed to the alleviation of fatigue in the body. Furthermore, the levels of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) were significantly increased (p < 0.05), which aided in mitigating oxidative damage induced by strenuous exercise. These findings strongly support the potential utilization of CFTHs in food products as natural antioxidant and anti-fatigue alternatives.